Compétition entre bâti et agriculture dans la conquête des bas-fonds de la ville de Bouaké : le savoir-faire ou les actions stratégiques des citadins-agriculteurs pour préserver les espaces agricoles - Jean-Michel Kouakou Attien Konan (VertigO)
Land is of crucial importance for housing in Ivoirian cities, just like in most African cities. Even areas non suitable for housing are more and more sought after. In the city of Bouaké, there is a growing competition over such areas, mainly shallows, between the housing sector and urban farmers. On the one hand, there is the housing sector that is pushing hard, by actively looking after shallows to expand its infrastructures. On the other hand, there is urban agriculture, that has been implemented and practiced for decades now, thanks to the skills of urban farmers, and which intends to be present in these urban wetlands for the long run.